The Implementation of School Counseling Supervision to Improve the School Counselor Performance - Hestiningtyan, Amianti Putri; Sugiyo, Sugiyo; Awalya, Awalya (Universitas Negeri Semarang, 2022)
School counselors performance affects the implementation of guidance and counseling services, particularly in providing guidance and solving students developmental problems in the field of personality, social, learning, and career based on their needs. This performance can be improved by having counseling supervision. Regarding this issue, the present study attempted to analyze the correlation between school counseling supervision implementation and the improvement of school counselors performance throughout Public Junior High Schools or SMP Negeri in Pemalang Regency. It used qualitative design with ethnography to study values, rules, and behaviors of a particular group or community. One school supervisor, two principals, and three school counselors inpublic schools were involved as the subjects of this study. Their data were collectedthough observation, interview, and documentation. Findings showed that the waythe supervisor supervised the schools was still in general. Even so, the supervisorhas already given some strategies to improvethe school counselors performance,but the implementation has not yet been optimum. Therefore, this study suggests the importance of continuous counseling supervision.